A Theoretical Framework for the Electrochemical Characterization of Anisotropic Micro‐Emulsions. Issue 17 (6th September 2021) - Tichter, Tim; Borah, Rohan; Nann, Thomas
Abstract: Micro emulsions (MEs) offer an exceptionally broad spectrum of applications covering sensing, electrosynthesis, supercapacitors and redox‐flow batteries. Herein, we develop the theory for a sophisticated electrochemical characterizion of MEs with a spatially and time‐invariant anisotropy in the diffusion domain by means of cyclic voltammerty (CV). By introducing spatially dependent diffusion coefficients into Ficks' first law, we derive a modified diffusion equation to simulate any inherent anisotropy of the ME under investigation. Moreover, by formulating an extended second‐order homogeneous six‐member square scheme for a kinetically controlled two‐step two‐electron reaction we capture the intricate entanglement of chemical and electrochemical equilibria. Our theoretical concept is finally validated by experimental CV data for the ME based two‐step redox reaction of methyl‐viologen which paves the way for a quantitative electrochemical characterization MEs. Abstract : The theory of kinetically controlled, diffusional cyclic voltammetry in anisotropic microemulsion‐electrolytes is derived by introducing spatially dependent diffusion coefficients and Butler‐Volmer kinetics into the extended homogeneous six‐member square scheme. Simulations are validated against experimental data for the two‐step redox reaction of methyl‐viologen in a micro‐emulsion of toluene in water, which is an important subject in the field of organic redox‐flow batteries.